Economic and financial resilience in a VUCA World: A conceptual framework for navigating uncertainty - Priya, Priya; Saxena, Ritu; Rohit, Rohit; Khyati, Khyati; Saxena, Rishi; Nanda, Anuj (The International tax journal, 2026)
In an era characterized by volatility, uncertainty, complexity, and ambiguity (VUCA), traditional economic and financial frameworks are increasingly inadequate for addressing dynamic global disruptions. This conceptual paper proposes an integrative framework for enhancing economic and financial resilience by synthesizing insights from resilience theory, behavioral finance, institutional economics, and digital transformation. The study critically examines how systemic shocks—such as financial crises, pandemics, geopolitical conflicts, and technological disruptions—reshape economic stability and financial decision-making processes. The proposed framework identifies key dimensions of resilience, including adaptive capacity, financial agility, risk intelligence, and institutional robustness. It emphasizes the role of data-driven decision-making, decentralized financial systems, and policy responsiveness in mitigating uncertainty. Furthermore, the paper highlights the growing significance of emerging technologies such as artificial intelligence, blockchain, and fintech ecosystems in strengthening financial resilience at both macroeconomic and microeconomic levels. By integrating theoretical perspectives with real-world contextual insights, this study contributes to the evolving discourse on sustainable economic systems in turbulent environments. The framework offers practical implications for policymakers, financial institutions, and businesses seeking to navigate uncertainty and build long-term resilience. It also outlines future research directions to empirically validate the proposed model across diverse economic contexts.